PENERAPAN KNOWLEDGE MANAGEMENT BERBASIS TEKNOLOGI INFORMASI PADA PERUSAHAAN - Tati Mardiana (Paradigma, 2008)
To organization management agents, managing assets of knowledge resource is a common task. Knowledge resources are closely related with human resource as the most important intellectual asset and capital for a company. Nevertheless, a company often forgets and does not realize the need of managing human resource asset to pose the development of management complexity, internal and external dynamics of the organization, management method and information technology. Human resource asset and intellectual capital are the main source of knowledge complete with organization experience of each person, which will be useful for achieving the organization goals in knowledge management. Competition demands a company to improve its creativity in increasing its competitive value. Knowledge management is a method by which a company creates and innovates rapidly. The company, therefore, can always have various sources and can improve its quality and value.